Risk Factors for Fractures of Dogs in Quezon City, Philippines - Biscante, Jerome; Oronan, Rey Barcenas; Calibo, Matthew Benedict (Universitas Airlangga, 2024)
A retrospective case-control study was conducted in dogs with bone fractures presented at the Veterinary Teaching Hospital - Diliman Station, Companion Animal Clinic, College of Veterinary Medicine, University of the Philippines Los Baños from January 2016 to December 2021. One hundred sixty-one dogs were diagnosed with bone fractures. Limping was the most common chief complaint with falling from a height being the most common cause. Close, complete, and oblique fractures were the most prevalent fracture type. Around 29.81% of the cases were given medications only and 16.77% were treated with external coaptation. Among the cases treated with external coaptation, only fourteen came back for follow-up with fully healed bone fractures. The mean age of dogs with bone fractures was 2.30 years old and was seen as a significant risk factor regardless of age group. Dogs fed with dry dog food and table food were 0.35 and 0.50 less likely to have bone fractures, respectively. The body weight, body condition scores, and dog breeds were not significant risk factors while the abode of the animal was a significant risk factor regardless whether the animal is indoor or outdoor. Age, diet, and abode were found to be significantly associated with bone fractures.